Influence of barley inclusion method and protease supplementation on growth performance, energy and nutrient utilisation and gastrointestinal tract development in broiler starters : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Manawatu, New Zealand - Tari, Lindon McEnroe (Massey University, 2020)
The influence of barley inclusion method and protease supplementation on the performance and coefficient of apparent ileal digestibility (CAID) of nutrients and energy and gastrointestinal tract development in broiler starters fed wheat-based diets from 1 to 21 days of age were examined in this study. A normal starch hulled barley was ground in a hammer mill to pass through the screen size of 2.5 mm and 8.0 mm. Three basal diets containing normal starch hulled barley, either finely ground (2.5 mm), coarsely ground (8.0 mm) or whole barley, were used to develop six dietary treatments either with or without protease enzyme. A total of 288 one-day-old male broilers (Ross 308) were individually weighed and allocated into 36 cages. Each of the six treatments was randomly assigned into six cages each housing eight birds. The pellet durability index (PDI) was higher (P < 0.05) in pellets made from diets based on finely ground barley than those made from coarsely ground or whole barley. The main effect of barley inclusion method was significant (P < 0.01) for weight gain and feed conversion ratio (FCR) from day 1 to 21. Birds fed diets containing coarse particles and whole barley showed higher (P < 0.05) weight gain compared to those fed diets containing fine particles. Feed conversion ratio was lower (P < 0.05) in birds fed whole barley compared to birds fed fine particles. Diets made from coarsely ground and whole barley had higher (P < 0.05) CAID of dry matter, nitrogen, calcium, and gross energy compared to the diets made from finely ground barley. Fine and coarse grinding increased (P < 0.05) CAID of phosphorus compared to whole barley diets. Diets made from fine and coarse barley had higher (P < 0.05) gizzard pH compared to those made from whole barley. Diets made from fine and coarse grinding increased (P < 0.05) the relative weight of proventriculus and decreased (P < 0.05) the relative weight of gizzard compared to whole barley diets. An interaction (P < 0.05) was observed for the relative weight of caeca. The relative weight of caeca was reduced numerically with protease supplementation in fine and coarse ground diets, whereas, in whole barley diets, protease supplementation numerically increased relative weights of caeca compared to diets without enzyme. The main effect of protease supplementation and interaction of barley inclusion method x protease supplementation were not significant (P > 0.05) for growth performance, nutrient digestibility, energy and nitrogen-corrected apparent metabolizable energy parameters. Overall, the present data showed that coarse grinding and whole inclusion of barley, through enhanced nutrient digestibility, are beneficial to the growth performance in broiler starters.
Keywords: 300301 Animal growth and development